α-MoO3 thin ﬁlms prepared by spray pyrolysis (2011)
In this work thin films of molybdenum trioxide (MoO3) were prepared by the pyrolytic atomization technique. The films were deposited on glass substrates and obtained from a precursor solution of Tetrahydrate Ammonium Heptamolybdate ((NH3) 6Mo7O24.4H2O) 0.1 M. The substrate temperature was kept constant at 400 oC and the volume of the solution was varied precursor The samples were characterized by X-ray diffraction (XRD), infrared spectroscopy, Scanning Electron Microscopy (SEM) and electrically through measurements of electrical resistivity as a function of temperature. The samples grow with crystalline structure corresponding to the alpha phase of MoO3 with preferential direction of growth along the planes (0k0). As the volume of the precursor solution increases, the surface of the samples becomes porous. The resistivity in these samples changes in an order of magnitude when they are exposed to the atmosphere of CO.